Agency theory, capital structure and firm’s performance : evidence from some selected shariah index companies in Malaysia / Siti Mursyidah Afiqah Abdullah - Abdullah, Siti Mursyidah Afiqah (Universiti Teknologi Mara Perlis, 2020)
Capital structure typically tells that it is a distribution of debt and equity to finance the overall operation and growth of a company. Meanwhile, agency theory describes the relationship between business principals and their agents. It also resolves the issues that arise among them. The relationship is usually between the shareholders that act as principals and the manager which act as agents. The objective of this study is to investigate the several factors affecting capital structure due to agency theory evidence from public listed Shariah index companies in Malaysia. This study uses panel regression analysis to conduct the results. In other way, the data collected is to measure the relationships or to establish the difference between groups. It is also the matter of testing the variables if it is causing another variable to change. As for this study, the researcher is going to test how does the leverage (TDR and TDER), size, growth and asset structure can make changes among themselves. It ensures that data collected related to the objectives of the study and that data analysis generated results that answered the research questions. Both ROA and ROE model determine that TDR and is the most significant variable with negative relationship respectively.